The Tyrosine Kinase Tec Regulates Effector Th17 Differentiation, Pathogenicity, and Plasticity in T-Cell-Driven Intestinal Inflammation - Sandner, Lisa; Alteneder, Marlis; Zhu, Ci; Hladik, Anastasiya; Högler, Sandra; Rica, Ramona; Van Greuningen, Lars W.; Sharif, Omar; Sakaguchi, Shinya; Knapp, Sylvia; Kenner, Lukas; Trauner, Michael; et al. (Frontiers in Immunology, 2021)
T helper (Th) 17 cells are key in controlling infections mediated by extracellular bacteria and fungi, but are also triggering auto-immune responses. Th17 cells comprise heterogeneous subsets, some with pathogenic functions. They can cease to secrete their hallmark cytokine IL-17A and even convert to other T helper lineages, a process known as transdifferentiation relying on plasticity. Both pathogenicity and plasticity are tightly linked to IL-23 signalling. Here we show that the protein tyrosine kinase Tec is highly induced in Th17 cells. Th17 differentiation was enhanced at low Interleukin-6 (IL-6) concentrations in absence of Tec, which correlates with increased STAT3 phosphorylation and higher Il23r expression. Therefore, we uncovered a function for Tec in the IL-6 sensing via STAT3 by CD4+ T cells, defining Tec as a fine-tuning negative regulator of Th17 differentiation. Subsequently, by using the IL-17A fate mapping mouse combined with in vivo adoptive transfer models, we demonstrated that Tec not only restrained effector Th17 differentiation but also pathogenicity and plasticity in a T cell intrinsic manner. Our data further suggest that Tec regulates inflammatory Th17-driven immune responses directly impacting disease severity in a T cell-driven colitis model. Notably, consistent with the in vitro findings, elevated levels of the IL-23 receptor (IL-23R) were observed on intestinal pre- and postconversion Th17 cells isolated from diseased Tec -/- mice subjected to adoptive transfer colitis, highlighting a fundamental role of Tec in restraining IL-23R expression, likely via the IL-6-STAT3 signaling axis. Taken together these findings identify Tec as a negative regulator of Th17 differentiation, pathogenicity and plasticity, contributing to the mechanisms which help T cells to orchestrate optimal immune protection and to restrain immunopathology.